Developing ELT materials for Muslim learners - Preece, Abdul Shakour Duncan; Mohd. Asraf, Ratnawati (American Scientific Publishers, 2017)
This paper discusses the need to develop ELT materials for Muslim learners and the importance, when developing these materials, of addressing the cognitive and affective domains, and for the materials to be rich in moral values so that they are able to provide a means for students to think, reflect upon, and discuss issues of relevance to them, which would lead to the inculcation of positive, universal, and Islamic values. It also discusses the need to develop critical thinking among students through ‘Community of Inquiry’ pedagogy that utilizes a discourse-based approach for philosophical issues of relevance to Muslim learners.